Light and nutrient control of photosynthesis in natural phytoplankton populations from the Chukchi and Beaufort seas, Arctic Ocean. (14th November 2013) - Palmer, Molly A.; van Dijken, Gert L.; Mitchell, B. Greg; Seegers, Brian J.; Lowry, Kate E.; Mills, Matthew M.; Arrigo, Kevin R.
Abstract : During the 2010–2011 'Impacts of Climate Change on the EcoSystems and Chemistry of the Arctic Pacific Environment' project, we measured photosynthetic parameters in natural Arctic phytoplankton assemblages from the Chukchi and Beaufort seas. Water‐column samples were taken from the near surface (3.1 ± 0.9 m) and subsurface (28 ± 10.3 m) at ∼ 85 stations each year representing a wide range of ecological conditions, including under sea ice (UI) and in open water (OW). The physiological response of phytoplankton to light was used to assess photo‐acclimation, photosynthetic efficiency, and maximum chlorophyll a (Chl a ) normalized rates of carbon fixation. Phytoplankton from the subsurface were acclimated to lower irradiance, as evidenced by higher photosynthetic efficiencies ( α * ), reduced mean absorption spectra ( ā * ) associated with heavy pigment packaging, higher maximum quantum yields of photosynthesis (Φ m ), increased Chl a content (Chl a : POC), and higher potential growth rates ( μm ) than surface samples. In addition, phytoplankton growing in the UI subsurface had higher μm, increased Φ m, and higher Chl a content, as well as reduced ā * compared with those found in OW. P * m did not vary between habitats despite vastly different nutrient and light conditions (averaging ∼ 1 mg C mg −1 Chl a h −1 ), except where nitrate exceeded > 10 mg m −3, in which case P * m averaged 5–6 mg C mg −1 Chl a h −1 . Results from a stepwise regression analysis of photosynthetic parameters vs. environmental factors indicate that the concentration of inorganic nitrogen (significant relationships with P * m, α *, Φ m, μm, and Chl a : POC) and temperature at sample depth (a strong indicator of habitat type; significant relationship with β *, ā *, Φ m, μm, and Chl a : POC) are the best predictors of photosynthetic variables. In addition, the amount of light available at sample depth significantly predicted both Ek and Chl a : POC. Our results suggest that it is the balance between light and nutrient availability in the various environments encountered in the seasonal sea ice zone that result in the pattern of photo‐physiological data presented here. A significant proportion of primary production has now been observed to occur under the sea ice; therefore, our results may be a change from prior conditions in the region.